Music in Renaissance Ferrara 1400-1505: The Creation of a Musical Centre in the Fifteenth Century - Lockwood, Lewis 1930- (Oxford Oxford University Press, 1984)
Based on extensive documentary and archival research,Music in Renaissance Ferrarais a study of the rise of music at a vital center of Italian Renaissance culture, focusing on the patrons and musicians whose efforts gave Ferrara a primary role in European music during the fifteenth century. The successive rulers of the Italian city-state, members of the Este dynasty, brought to Ferrara some of the most important composers of the period, including Guillaume Dufay, Johannes Martini, Jacob Obrecht, and Josquin Desprez. Moreover, Ferrara has long been famous as the seat of activity of three of the most important poets of the period - Boiardo, Ariosto, and Tasso - as well as for its school of painting and manuscript production and illumination. With Lewis Lockwood's Music in Renaissance Ferrara, the city-state steps forward as a major musical center as well.
Keywords: Renaissance (1400-1600); Music history; Ferrara (Italy)